2016
DOI: 10.2460/javma.249.12.1408
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of sterile hemorrhagic cystitis in tumor-bearing dogs concurrently treated with oral metronomic cyclophosphamide chemotherapy and furosemide: 55 cases (2009–2015)

Abstract: OBJECTIVE To determine the incidence of sterile hemorrhagic cystitis (SHC) in tumor-bearing dogs concurrently treated with oral metronomic cyclophosphamide chemotherapy and furosemide. DESIGN Retrospective case series. ANIMALS 55 dogs. PROCEDURES Record databases of 2 specialty practices were searched to identify dogs treated with oral metronomic cyclophosphamide chemotherapy in conjunction with furosemide for a minimum of 28 days between January 2009 and December 2015. Information extracted from the records i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 26 publications
0
23
0
2
Order By: Relevance
“…Furosemide may reduce the incidence of cystitis when given concurrently (Charney et al, 2003;Best and Fry, 2013) and thus was suggested in this case. A small study also suggested similar benefit in low-dose or metronomic cyclophosphamide scheduling which is more akin to the treatment given in the current case (Chan et al, 2016).…”
Section: Introductionmentioning
confidence: 55%
“…Furosemide may reduce the incidence of cystitis when given concurrently (Charney et al, 2003;Best and Fry, 2013) and thus was suggested in this case. A small study also suggested similar benefit in low-dose or metronomic cyclophosphamide scheduling which is more akin to the treatment given in the current case (Chan et al, 2016).…”
Section: Introductionmentioning
confidence: 55%
“…The overall incidence of SHC in the University of Wisconsin‐Madison dogs enrolled in this study was 8.9%. This is comparable to other studies, in which SHC was found in 3.8% to 9.0% of pulse‐treated dogs, and in 3.6% to 32% of metronomic CP‐treated dogs Metronomic CP was a significant risk factor for SHC in our study. Cumulative CP doses were nearly 3‐fold higher with metronomic compared to pulse protocols, and higher cumulative doses are a risk factor for SHC .…”
Section: Discussionmentioning
confidence: 92%
“…For each dog, the following data were recorded: signalment, tumour type, CP dosing and frequency, route of administration, cumulative CP dose, and clinical outcomes of SHC, myelosuppression or GI toxicity. Concurrent drug administration was recorded, including NSAIDs and furosemide or prednisone …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sterile hemorrhagic cystitis (SHC), commonly reported with the use of cyclophosphamide, was not observed in this study. Chan et al (2016) used furosemide concurrently with cyclophosphamide during MC and suggested that furosemide protects against cyclophosphamide-induced SHC.…”
Section: Discussionmentioning
confidence: 99%